Peran Penyuluh Agama Kristen Kantor Kementerian Agama Kabupaten Seram Bagian Barat pada Wilayah Binaan - Risakotta, Rizky Nelson (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper outlines the role of Christian Religious Counselors from the Ministry of Religious Affairs Office in West Seram Regency in guiding spirituality and Christian values within their assigned areas. The study identifies significant challenges they face, including weak inter-agency coordination, minimal synergy with other institutions and religious organizations (ormas), and subpar counseling materials coupled with inadequate counselor skills. The study aims to analyze the effectiveness of these Christian Religious Counselors in their work areas, investigate the problems encountered, and formulate comprehensive policy recommendations to boost their effectiveness. This paper uses a descriptive qualitative method with a case study approach to dissect the identified core issues. Findings indicate that weak inter-agency coordination is the most pressing problem among the challenges. Overall, the study confirms that the counselors' effectiveness remains suboptimal due to a combination of issues across coordination, synergy, materials, and skills. The recommended policy for the Ministry of Religious Affairs Office in West Seram Regency is to propose a Draft Regional Regulation (Raperda) on Strengthening the Role of Religious Counselors. This legal instrument will legitimize and institutionalize cross-agency collaboration and local government support for counseling duties. Its goal is to ensure that religious development, especially counseling, has strong legal backing and comprehensive support in West Seram Regency.